2015
DOI: 10.1007/s12078-015-9180-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory Science in the Context of Cancer Treatment: Implications for Patient Care

Abstract: Introduction This collaborative commentary brings together both clinical and sensory science perspectives in an effort to explain the mechanisms of cancer treatment and the ensuing implications for the sensorium. Strategy This paper makes the distinction between food hedonics and true chemosensory effects in the cancer context and describes the adverse effects cancer and its treatment have on the eating and drinking experience, including gastronomic, nutritional and emotional implications. Results from a prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
(39 reference statements)
3
8
0
Order By: Relevance
“…Thus, in this matter, knowledge and interest in food and cooking constituted an individual resource. Strategies such as avoiding unpleasant odors, adjusting seasonings, and trying out foods are similar to previous research reports’ suggestions for how health care professionals might better support patients with TSAs [ 29 , 30 ]. As some participants in our study had resources to initiate these strategies by themselves, such advice was sometimes perceived as superfluous.…”
Section: Discussionsupporting
confidence: 74%
“…Thus, in this matter, knowledge and interest in food and cooking constituted an individual resource. Strategies such as avoiding unpleasant odors, adjusting seasonings, and trying out foods are similar to previous research reports’ suggestions for how health care professionals might better support patients with TSAs [ 29 , 30 ]. As some participants in our study had resources to initiate these strategies by themselves, such advice was sometimes perceived as superfluous.…”
Section: Discussionsupporting
confidence: 74%
“…Commencing chemotherapy has also been identified as a timely opportunity for receiving information about diet and weight management (James-Martin et al, 2014;Heinze and Williams, 2015;Kelly et al, 2015). Improving nutrition in women during chemotherapy may provide benefits such as enhancing general health and wellbeing (Lawn et al, 2015); enabling women to better cope with chemotherapy side effects (Breast Cancer Care 2014; Boltong and Keast, 2015); and reducing the subsequent risk of cancer recurrence (Tramm et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism underlying these chemosensory alterations is not yet known owing to the multifactorial etiology of taste and odor abnormalities. It has been suggested that chemotherapy targets rapidly dividing cancer cells, but unfortunately, this systemic treatment is not selective, and other rapidly growing non‐cancer cells, such as mucosal cells and olfactory and gustatory receptors, are also damaged …”
Section: Introductionmentioning
confidence: 99%